Frontispiece: Self‐Assembly of Semiconductor Quantum Dots using Organic Templates. Issue 32 (5th June 2020) - Yamauchi, Mitsuaki; Masuo, Sadahiro
Abstract : Self‐assembly of semiconductor quantum dots are realized by mixing organic template molecules with adhesion moieties to the surface of quantum dots. This Minireview highlights the strategies for the formation of assembled quantum dots such as dimers and trimers and extended assemblies, and their photophysical properties. For more information, see the Minireview by M. Yamauchi and S. Masuo on page 7176 ff.